2020
DOI: 10.1007/s11250-020-02256-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of birth weight trait in dromedary camels (Camelus dromedarius)

Abstract: Birth weight data of dromedary calves from the database of one of the world's largest dairy herds (Dubai, UAE) were analyzed for the period from 2007 to 2018. The assessment included the data of 4124 camel calves that were classified into six ecotypes (Emirate, Emirate crossed, Black, Pakistanian, Saudi-Sudanian, and Saudi crossed). The aim of the study was to describe the heritability of birth weight of calves and the breeding value of sires. Genetic parameters of birth weight were estimated by ANOVA model an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(54 reference statements)
0
4
1
Order By: Relevance
“…In summary, it can be concluded that the dromedary camel's h 2 d of GL was similar to values in cattle but higher than those in horses, the h 2 m of GL was similar to values in cattle but lower than those in horses, the r dm value was similar to values in horses but lower than those in cattle, and the c 2 of GL was higher than those in cattle and horses. In this study, the genetic parameters of GL of dromedary camels were partially different from those published for BW of camels previously (Bene et al, 2020). In case of GL the h 2 d was higher, the h 2 m was lower and the c 2 was slightly lower that those observed for the BW of camels.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…In summary, it can be concluded that the dromedary camel's h 2 d of GL was similar to values in cattle but higher than those in horses, the h 2 m of GL was similar to values in cattle but lower than those in horses, the r dm value was similar to values in horses but lower than those in cattle, and the c 2 of GL was higher than those in cattle and horses. In this study, the genetic parameters of GL of dromedary camels were partially different from those published for BW of camels previously (Bene et al, 2020). In case of GL the h 2 d was higher, the h 2 m was lower and the c 2 was slightly lower that those observed for the BW of camels.…”
Section: Discussioncontrasting
confidence: 91%
“…The present study is a continuation of our earlier work (Bene et al, 2020) on dromedary camels. Due to the similarity between the database and methods used, some details of the Materials and Methods described in our previous publication will not be repeated here.…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…During the current course of the study, it was observed that birth weight of camels significantly affected their productive potential. Birth weight data of dromedary calves from the database of one of the world's largest dairy herds Dubai, UAE, was evaluated by Bene et al (2020). Based on the results of this study, they concluded that the birth weight of dromedary calves was more influenced by the dam's intrauterine rearing capacity and by the environment, management and feeding of the pregnant female camels than the hereditary growth potential.…”
Section: Productive Parametersmentioning
confidence: 99%
“…Estimates of heritability, repeatability and breeding values of meat yield, milk yield, growth measures, reproductive and adaptive traits are lacking in African camels, unlike in others ( Bene et al, 2020 ). The only available information was obtained on 302 records on lactation over a 10-year period for a herd of camels in Egypt with respect to total milk yield (TMY), day milk yield (DMY) and length of lactation period (LP).…”
Section: Genetic Parameters Estimationmentioning
confidence: 99%